Role of Insulin and Adenosine in the Human Placenta Microvascular and Macrovascular Endothelial Cell Dysfunction in Gestational Diabetes Mellitus. (January 2014) - Guzmán‐Gutiérrez, Enrique; Arroyo, Pablo; Salsoso, Rocío; Fuenzalida, Bárbara; Sáez, Tamara; Leiva, Andrea; Pardo, Fabián; Sobrevia, Luis
Abstract Microvascular and macrovascular endothelial function maintains vascular reactivity. Several diseases alter endothelial function, including hypertension, obesity, and diabetes mellitus. In addition, micro‐ and macrovascular endothelial dysfunction is documented in GDM with serious consequences for the growing fetus. Increased l‐arginine uptake via hCAT‐1 and NO synthesis by eNOS is associated with GDM. These alterations are paralleled by activation of purinergic receptors and increased umbilical vein, but not arteries blood adenosine accumulation. GDM associates with NO‐reduced adenosine uptake in placental endothelium, suggested to maintain and/or facilitate insulin vasodilation likely increasing hCAT‐1 and eNOS expression and activity. It is proposed that increased umbilical vein blood adenosine concentration in GDM reflects a defective metabolic state of human placenta. In addition, insulin recovers GDM‐alterations in hCAT‐1 and eNOS in human micro‐ and macrovascular endothelium, and its biological actions depend on preferential activation of insulin receptors A and B restoring a normal‐like from a GDM‐like phenotype. We summarized existing evidence for a potential role of insulin/adenosine/micro‐ and macrovascular endothelial dysfunction in GDM. These mechanisms could be crucial for a better management of the mother, fetus and newborn in GDM pregnancies.